HBP/O-GlcNAcylation Metabolic Axis Regulates Bone Resorption Outcome. (April 2023) - Taira, T.M.; Ramos-Junior, E.S.; Melo, P.H.; Costa-Silva, C.C.; Alteen, M.G.; Vocadlo, D.J.; Dias, W.B.; Cunha, F.Q.; Alves-Filho, J.C.; Søe, K.; Fukada, S.Y.
Osteoclasts play a key role in the regulation of bone mass and are highly active metabolically. Here we show that a metabolic reprogramming toward the hexosamine biosynthetic pathway (HBP) is required not only for osteoclast differentiation but also to determine the bone resorption mode during physiological and pathological bone remodeling. We found that pharmacological inhibition of O-GlcNAc transferase (OGT) significantly reduced protein O-GlcNAcylation and osteoclast differentiation. Accordingly, genetic deletion of OGT also inhibited osteoclast formation and downregulated critical markers related to osteoclasts differentiation and function (NFATc1, αv integrin, cathepsin K). Indeed, cells treated with OSMI-1, an OGT inhibitor, also reduced nuclear translocation of NFATc1. Furthermore, the addition of exogenous N-acetylglucosamine (GlcNAc) strongly increased osteoclast formation and demineralization ability. Strikingly, our data show for the first time that O-GlcNAcylation facilitates an aggressive trench resorption mode in human cells. The incubation of osteoclasts with exogenous GlcNAc increases the percentage of erosion by trench while having no effect on pit resorption mode. Through time-lapse recording, we documented that osteoclasts making trenches moving across the bone surface are sensitive to GlcNAcylation. Finally, osteoclast-specific Ogt -deficient mice show increased bone density and reduced inflammation-induced bone loss during apical periodontitis model. We show that osteoclast-specific Og t-deficient mice are less susceptible to develop bacterial-induced periapical lesion. Consistent with this, Ogt -deleted mice showed a decreased number of tartrate-resistant acid phosphatase-positive cells lining the apical periodontitis site. In summary, here we describe a hitherto undiscovered role of the HBP/O-GlcNAcylation axis tuning resorption mode and dictating bone resorption outcome.